Estado nutricional de pré-escolares: Efeito da suplementação de uma mistura de alimentos convencionais e não convencionais - Cintra, Renata Maria Galvao de Campos [UNESP]; Soares, Sérgio Eduardo; Dias, Luiza Cristna Godim Domingues [UNESP]; Marconato, Mara Silvia Foratto (My University, 2010)
This study aimed to evaluate the effect of supplement with unconventional and conventional low-cost foods, the latter was called “multi-mixture”, on the nutritional status of preschool children. During 11 weeks, 106 preschool children received multi-mixture (15g/dia). Anthropometric and biochemical findings were obtained at the beginning and end of this period. All procedures were approved by the Board of Ethics in Research, and the personnel responsible for the service agreed to its realization by signing the Consent Form. We used the indexes weight for age (W/A), weight for height (W/H), height for age (H/A) and BMI, and the biochemical indexes: total protein and albumin to assess nutritional status. The diagnostic criterion used was Z score for H/A, W/A and W/H, and percentile values for BMI. Initial results have identified low H/A, W/A and W/H in 6%, 4% and 2% of the preschool children, respectively. In 10% of the children was observed BMI below the 5th percentile, however 30% had BMI above the 85th percentile, indicating overweight in the population. Albumin presented to be adequate for 100%, and total protein to 98% of the population. After the supplementation period, the indices H/A, W/A and W/H were low at 4%, 4% and 2% respectively. According to BMI, there were 13% of children with values lower than expected after supplementation. The concentrations of total protein or albumin were not significantly altered by supplementation. The anthropometric or biochemical indicators do not point to beneficial effects of multi-mixture on the nutritional status of in preschool children, or even changes in the prevalence of overweight.

Esse trabalho teve como objetivo avaliar o efeito de suplemento com alimentos não convencionais e convencionais de baixo custo, denominado multimistura, sobre o estado nutricional de pré-escolares. Durante 11 semanas, 106 pré-escolares receberam multimistura (15g/dia), sendo indicadores antropométricos e bioquímicos obtidos no início e ao final do período. Todos os procedimentos foram aprovados pelo Comitê de Ética em Pesquisa, e os responsáveis consentiram na sua realização por meio do Termo de Consentimento Livre Esclarecido. Utilizou-se os índices peso para idade (P/I), peso para altura (P/A), estatura para idade (E/I) e o IMC; e índices bioquímicos: proteínas totais e albumina para avaliação nutricional. Como critério diagnóstico utilizou-se escore Z para E/I,, P/I e P/E, e valores de percentis para IMC. Os resultados iniciais identificaram baixo E/I, P/I e P/E em 6%, 4% e 2% dos pré-escolares, respectivamente. Em 10% das crianças foi observado IMC abaixo do percentil 5, entretanto 30% apresentaram IMC acima do 85º percentil, evidenciando o excesso de peso na população. Albumina apresentou-se adequada para 100%, e proteína totais para 98% da população. Após o período suplementação, os índices E/I, P/I e P/E foram baixos em 4% , 4% e 2%, respectivamente. Segundo o IMC, houve 13% das crianças com valores abaixo do esperado após a suplementação. As concentrações de proteínas totais ou albumina não foram alteradas significativamente pela suplementação. Os indicadores antropométricos ou bioquímicos não apontam para efeitos benéficos da multimistura no estado nutricional de crianças em fase pré-escolar, ou mesmo mudanças na prevalência de excesso de peso.
The nutritional status of pre school children: the effect of supplementation with conventional and nonconventional food mixture
Keywords: Pre-school; Nutritional status; Multimixture; Pré-escolares; Multimistura; Avaliação nutricional